(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Succession is the most complex and turning point in thelife span of a family business, because it not only involves money, it involvesrelations and emotions. The succession planning involves three situations,depending upon number of successors. Based on his experience, the author listshow to plan, succession in a family business.